Slavic but not Russian: invisible and mute - Thompson, Ewa (Porównania, 2015)
The paper argues that the non-Russian Slavic Studies at American universities exist only virtually. The number of non-Russian Slavic specialists is pitifully small and incommensurate with East Central Europe’s strategic location and cultural identity, while the generally accepted format of university hiring and firing perpetuates this state of affairs. Among characteristic instances is affirmative action concerning certain narrow areas of study, side by side with delayed action (or no action at all) in non-Germanic Central and Eastern European Studies; a pattern of not reviewing in professional journals books